Students’ Response to Literature as Experience in Aesthetic Reading of Narrative Text - Pupun Robiah Mutmainah (Journal of English Education Program (JEEP), 2015)
This article centered around the issues of students’ responses to literature as experience in aesthetic reading of narrative text. The aims of this study are to identify the kinds of students’ responses that dominant in aesthetic reading of narrative text and to acknowledge the strategies of response which dominant in aesthetic reading of narrative text. Qualitative approach was employed in this research by using a case study, and data were collected through observation and open-ended questionnaire. The research has found that the kinds of students’ response dominant used by students in aesthetic reading of narrartive text was focusing on part type 18 participants (57% respondents) and the strategies of response dominant used by students in aesthetic reading of narrative text was engaging strategy (33 sentences). This research concludes that the reader response can used as a strategy and aesthetic reading used as an approach in teaching learning literature.